Factors Affecting Teacher Motivation in Nepal - Khanal, Peshal; Phyak, Prem (AMC Journal, 2021)
The major aim of this paper is to report the finding of a study that aims at analyzing different factors influencing teacher motivation towards the teaching profession. To this goal, a mixed method approach was used and quantitative data were collected from 430 teachers, teaching at the Basic Level, from six districts using a set of questionnaires. Qualitative data were gathered from 48 teachers, six resources persons, six teacher trainers and three policy-makers. The major findings of the study show that multiple factors influence teacher motivation towards teaching profession, which are broadly categorized under four areas: individual, school related, socio cultural and political. Policy-related factors include salary and benefits, leave facility, promotion, training, pensions and freedom to trade union. Similarly, school-related factors for teacher motivation include school management, leadership, teaching load, professional development opportunities and feedback and reinforcement mechanism. Student-related factors contain class size, student composition, regularity, and discipline. Socio-cultural factors for teacher motivation include social recognition of teachers, political interference and teacher-parent cooperation. Finally, the issue of teacher performance and motivation should be tied up with the policies of teacher professional development.